Working for justice : a handbook of prison education and activism - Hartnett, Stephen J.; Novek, Eleanor; Wood, Jennifer K. (University of Illinois Press, 2013)
This book contains practical approaches to prison education and advocacy. This collection documents the efforts of the Prison Communication, Activism, Research, and Education collective (PCARE) to put democracy into practice by merging prison education and activism. Through life-changing programs in a dozen states (Arizona, Colorado, Illinois, Indiana, Massachusetts, Michigan, New Jersey, Ohio, Pennsylvania, Texas, Virginia, and Wisconsin), PCARE works with prisoners, in prisons, and in communities to reclaim justice from the prison-industrial complex. The materials in this volume present a sweeping inventory of how communities and individuals both within and outside of prisons are marshaling the arts, education, and activism to reduce crime and enhance citizenship. Documenting hands-on case studies that emphasize educational initiatives, successful prison-based programs, and activist-oriented analysis, this book provides readers with real-world answers based on years of activism and teaching.